PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS OF CREATING AN INCLUSIVE ENVIRONMENT IN TEACHING PHYSICS - Dilruxsor Masodiqova (Modern American Journals, 2025)
This article explores the pedagogical and psychological foundations necessary for creating an inclusive environment in the teaching of physics. It emphasizes the significance of inclusive education in the context of modern educational reforms in Uzbekistan, particularly focusing on the integration of students with diverse needs into mainstream physics classrooms. The paper outlines effective teaching strategies, adaptive methods, and classroom practices that promote equal participation, motivation, and academic success among all learners. Special attention is given to the psychological readiness of teachers, the use of differentiated instruction, and the role of empathy in inclusive pedagogical practices. The research is supported by both theoretical insights and practical case examples drawn from local schools and higher education institutions in Uzbekistan.
Keywords: Inclusive education, teaching physics, pedagogical foundations, psychological support, differentiated instruction, special needs, educational environment, accessibility, teacher preparation, motivation, student diversity, classroom strategies, empathy, adaptation.